From Vision to Impact: How Africa Can Deliver on its AI Strategy - Ogot, Madara (UbuntuNet Alliance for Research and Education Networking, 2025)
The African Union (AU) Artificial Intelligence (AI) Strategy (2024) aims to catalyse inclusive AI-enabled growth and safeguard sovereignty, individual and organisational rights (African Union, 2024). The Hierarchy of Engagement with AI (HE-AI) model (Ogot, 2025) offers a practical framework for its implementation. The model frames individual and organisational engagement with AI as a progression along eight maturity levels. It integrates technical capability, governance, ethics, workforce, and ecosystem collaboration into a manageable and measurable stage-gated journey. Executing the Strategy's goals requires a staged evidence-based pathway that the HE-EI model provides. The model's sequenced logic, aligned with the Strategy's phased plan, will support its implementation.
Keywords: African Union; Artificial Intelligence; Maturity Model